WORKSHOP PENULISAN ARTIKEL ILMIAH BAGI GURU SMA/SMK/MA DI KABUPATEN BALANGAN - Muh. Waskito Ardhi; Dwi Rosita Sari; Yunita Furinawati; Muh.Nur Luthfi Azis; Davi Apriandi; Candra Dewi (Jurnal Terapan Abdimas, 2026)
Abstract. The scientific article writing workshop is a community service activity aimed at improving the understanding and skills of high school, vocational high school, and Islamic high school teachers in Balangan Regency, South Kalimantan, particularly in writing scientific articles based on Classroom Action Research (PTK). This event was held on February 19–21, 2024, through a collaboration between PGRI University of Madiun (UNIPMA), the Balangan High School and Vocational School Principals’ Association (MKKS SMK/SMA Balangan), and Light Community. The workshop included presentations on conceptual material and technical aspects of writing, as well as hands-on guidance on drafting. Of the 31 teachers in attendance, 26 participants completed pre- and post-activity comprehension questionnaires. The results of the evaluation analysis showed an increase in the average comprehension score from 2.33 to 3.29 per item, with a Normalized Gain (N-Gain) score of 0.573, which falls into the moderate category. The Shapiro-Wilk normality test indicated that the distribution of paired data differences was normally distributed (W=0.980; p=0.877). Therefore, a parametric Paired t-test was used, which yielded a highly significant difference (t(25)=11.417; p<0.001). This community service project concludes that the workshop proved to be effective and impactful in improving teachers’ understanding, particularly regarding the technical aspects of scientific article writing, which had previously been the participants’ main challenge. As a follow-up, it is recommended that ongoing clinical mentoring be provided until the manuscript submission stage. Abstrak. Workshop penulisan artikel ilmiah ini merupakan kegiatan pengabdian kepada masyarakat yang bertujuan untuk meningkatkan pemahaman dan keterampilan guru tingkat SMA/SMK/MA di Kabupaten Balangan, Kalimantan Selatan, khususnya dalam menyusun artikel ilmiah berbasis Penelitian Tindakan Kelas (PTK). Kegiatan ini diselenggarakan pada tanggal 19–21 Februari 2024 melalui kolaborasi antara Universitas PGRI Madiun (UNIPMA) dengan MKKS SMK/SMA Balangan dan Light Community. Pelaksanaan workshop meliputi penyampaian materi konseptual, aspek teknis penulisan, dan pendampingan praktik penyusunan artikel. Tercatat dari 31 guru yang hadir, sebanyak 26 peserta melengkapi angket pemahaman sebelum dan sesudah kegiatan. Hasil analisis evaluasi menunjukkan adanya peningkatan rata-rata skor pemahaman dari 2,33 menjadi 3,29 per butir, dengan skor Normalized Gain (N-Gain) sebesar 0,573 yang termasuk dalam kategori sedang. Uji normalitas Shapiro-Wilk menunjukkan distribusi selisih data berpasangan berdistribusi normal (W=0,980; p=0,877). Oleh karena itu, digunakan uji parametrik Paired t-test yang menghasilkan perbedaan sangat signifikan (t(25)=11,417; p<0,001). Adapun simpulan dari pengabdian ini adalah workshop terbukti efektif dan berdampak dalam meningkatkan pemahaman guru, terutama pada aspek teknis anatomi penulisan artikel ilmiah yang sebelumnya menjadi kendala utama peserta. Sebagai tindak lanjut, disarankan adanya pendampingan klinis berkelanjutan sampai tahap pengiriman naskah.